Republic of Ecuador Country Environmental Analysis : Environmental Quality and Natural Resource Management for Sustained Economic Growth and Poverty Alleviation - World Bank (Washington, DC, 2013)
Ecuador is a country with exceptional natural resource and environmental advantages and challenges. It is strategically located and has considerable oil reserves in the interior and the coastal region. This document does not aim to describe the state of the environment in Ecuador. Rather, its main objective is to provide an analytical foundation to identify the country's institutional weaknesses and provide practical policy options that will enhance its capacity to establish and address environmental policy priorities linked to poverty reduction and sustained economic growth. Linking environmental considerations to sectoral projects and policies will provide important information on key synergies and tradeoffs involving the environment, economic growth, and poverty. The second objective is to guide environmental assistance and capacity building supported by the bank or other development partners through the assessment of capacity issues, especially in relation to specific environmental priorities. The main elements of the Country Environment Analysis (CEA) include analyses of: a) environment and natural- resource-related institutions, b) the environmental aspects of the oil sector, c) forestry, d) conservation, e) environmental-health, and f) climate change. The CEA also identifies policy recommendations and describes the role that the World Bank could play in helping the Government of Ecuador (GOE) strengthen its institutional capacity in order to address the country's natural resource and environmental problems in a more effective way.